2005
DOI: 10.1097/01.ico.0000151564.24989.38
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antireflection Film Use on Blink Rate and Asthenopic Symptoms during Visual Display Terminal Work

Abstract: Visual display terminal work appears to be associated with asthenopic symptoms and decreased blink rates. The use of AR films on computer displays may prevent both reflections of light from screen surfaces and reduction in blink rates resulting in fewer asthenopic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 5 publications
0
23
1
Order By: Relevance
“…Their study also has shorter duration of near task compared to the present study. Even though 20 min of near task in the present study seem longer compared to previous studies, [2][3][4]8 it is still considered short compared to a study by Teoh et al 5 where subjects had 2 h of VDU tasks. The difference in their subjects' mean NIBUT was 3.71 s. It is possible that the short duration task in this study had resulted in the relatively small difference of preand post-task NIBUT (mean difference = 1.20 s, preclear NIBUT = 6.59 and post -CLEAR NIBUT = 5.39 s).…”
Section: Discussioncontrasting
confidence: 47%
“…Their study also has shorter duration of near task compared to the present study. Even though 20 min of near task in the present study seem longer compared to previous studies, [2][3][4]8 it is still considered short compared to a study by Teoh et al 5 where subjects had 2 h of VDU tasks. The difference in their subjects' mean NIBUT was 3.71 s. It is possible that the short duration task in this study had resulted in the relatively small difference of preand post-task NIBUT (mean difference = 1.20 s, preclear NIBUT = 6.59 and post -CLEAR NIBUT = 5.39 s).…”
Section: Discussioncontrasting
confidence: 47%
“…An increase in ocular symptoms during use of electronic devices and VDTs is well documented 31,32. It has been reported that 70% of VDT users experience some visual symptoms 33.…”
Section: Discussionmentioning
confidence: 99%
“…Eye problems, constituting a widespread but largely unknown epidemic among computer users, are the most common symptoms [25-30]. Dry eye is a common cause of, or is at least associated with, greater asthenopia symptoms among VDT workers [31-35]. Clinical observations have long suggested that VDT users may be at increased risk of developing dry eye disease [2,15,36], and epidemiologic data evidence the magnitude of the problem [36-38].…”
Section: Introductionmentioning
confidence: 99%